Analisis Beberapa Faktor yang Mempengaruhi Produksi Crude Palm Oil di Pabrik Kelapa Sawit PT SH Kalimantan Tengah - Sebayang, Denny Swadaya Putra; Ruswanto, Adi; Astuti, Yohana Theresia Maria (Politeknik Negeri Lampung, 2025)
The palm oil mill of PT SH located in Lamandau district, Central Kalimantan province, with an actual capacity of 50 tons of oil palm fruit bunches per hour, experiences problems such as the availability of fresh fruit bunch supply that is not optimal according to the factory capacity, the processing process is not smooth. There is often downtime due to damage to the machine unit during factory operation. This study aims to examine (1) the effect of fresh fruit bunches (amount or tonnage processed), (2) the effect of processing capacity (mill throughput), (3) the effect of downtime, and (4) the effect of processing costs on crude palm oil (CPO) production at the palm oil mill of PT SH by focusing on crude palm oil production as the dependent variable, then the number of fresh fruit bunches (FFB) processed, processing capacity, downtime, and processing costs as independent variables. The method used is multiple linear regression analysis modified from the Cobb-Douglas equation. The results of this study show that the factors of the number of FFB processed and processing capacity have a significant effect on CPO production. In contrast, downtime and processing costs do not significantly affect CPO production.